A Comparison of Antifungal Drugs and Traditional Antiseptic Medication for Otomycosis Treatment: A Systematic Review and Meta-Analysis - Wu, Shunyu; Cheng, Yin; Lin, Shunzhang; Liu, Huanhai (Frontiers in Surgery, 2021)
Objectives/Hypothesis: To perform a systematic review and meta-analysis to compare the efficacy of and complications associated with antifungal drugs and traditional antiseptic medication for the treatment of otomycosis. Data Sources: The PubMed, EMBASE, GeenMedical, Cochrane Library, CBM, CNKI, VIP and other databases were searched from January 1991 to January 2021. Methods: The systematic literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials (RCTs) and non-randomized studies (case-control, cohort, and case series) were included to assess the topical use of antifungal drugs and traditional antiseptic medication in patients with otomycosis. The research subjects were patients who were clinically diagnosed with otomycosis and whose external auditory canal secretions were positive for fungi. Funnel plots were used to detect bias, and the Q test was used to assess heterogeneity. The random-effects model was used for meta-analysis. The T test was used to assess significance. Results: Of the 324 non-duplicate studies screened, 16 studies met the criteria for full-text review, and 7 were included in the meta-analysis. Four studies reported recovery conditions (P=0.01). Six common complications after medication use were compared, and there were no significant differences. The authors further conducted subgroup analysis according to complications. The differences in the rates of ear distension (P=0.007), earache (P=0.03) and tinnitus (P=0.003) were statistically significant. Conclusion: The results of this meta-analysis and literature review showed that antifungal drugs and traditional antiseptic medication were effective in relieving symptoms in patients with otomycosis, and the two treatments were associated with different complications. Otolaryngologists have the option to use one medication or a combination of two drugs on the basis of the condition. Future research in this area should include RCTs with long-term follow-up to guide the development of otomycosis guidelines to overcome some of the weaknesses found in the literature.